Café Web Based System Using Priority Scheduling Approach - Fatimah, Ghazali; Rohana, Ismail; Mohamad Hariz, Hasni (2017)
Manual ordering system requires on many staffs to handle ordering process. It can be tedious and messy, and can end up with data inconsistency for generating sales report. Moreover, the total time taken for food preparations is longer. Therefore, the web based system is developed using priority scheduling algorithm to reduce the time taken in ordering process, handling and preparing bulk and concurrent order, and at the same time minimizing the cost of handling staffs. The priority scheduling algorithm is based on Control Processing Unit scheduling algorithm where it has a priority to execute tasks. The system is implemented at UniSZA’s café where two different types of user will use the system. The JSP, JavaScript, Java and MySQL have been employed to improve manual ordering management. Initially, the preliminary testing shows that the priority scheduling algorithm has a potential to replace the manual ordering system.